Air Quality Survey of some locations in the Niger Delta Area - A Adoki (Journal of Applied Sciences and Environmental Management)
A survey of air quality in Oyigbo (Obigbo) and environs in the Niger delta area of Nigeria revealed that air quality in the area is affected to varying degrees by industrial, human and natural activities. Results indicate that SOx values were below acceptable values for ambient conditions at most of the locations. The annual average SOx levels ranged between 92.0μg/m3 and 430μg/m3 against the DPR limit of 150μg/m3. A similar trend was observed for NOx emissions whose annual averages ranged between 81.0μg/m3 and 150μg/m3. Levels of these atmospheric contaminants were influenced by season. The average acidity values (5.63, 5.57, 5.41 and 5.41) of rainwater collected over the monitored period show rain acidity. The low Conductivity values however indicated non-contamination of the rainwater.